Integration
Integration
Integration
dz
1. (a) Substitute z = 2x2 − 3, = 4x.
dx
1 dz 1
∴ x dx = dx = dz
4 dx 4
R 51 z6 (2x2 − 3)6
∴I = z dz = +k = +k
4 24 24
(b) Substitute u = 9 − z 2 , −2z dz = du.
R 1 1 3 1 3
∴I = u 2 (− 2 ) du = − 12 u 2 23 + k = − (9 − z 2 ) 2 + k
3
(c) Substitute z = 3 − 2v.
(d) Substitute z = 4 − 5t.
(e) Substitute z x2 . =
sin 3x 1 sin 3x
(f) tan 3x sec 3x = = .
cos 3x cos 3x cos2 3x
dz
Substitute z = cos 3x, = −3 sin 3x
dx
∴ dz = −3 sin 3x dx
sin 3x dx 1 1 1 1
Z Z
I = = − dz = +k = sec 3x + k
cos 3x
2 z 2 3 3z 3
(g) cos2 x = 1 − sin2 x.
Z π/2
(1 − sin2 x) cos x
I = dx
π/6 sin x
dz
Put z =sin x, = cos x
dx
π π 1
Limits: x = ⇒ z = 1; x= ⇒ z=
2 6 2
1 1
1 − z2 z2
1 1
Z
I = dz = ln z − = ln 2 − + = 0.3181
1
2
z 2 1 2 8
2
1
dx
2. Put x = 2 sin θ = 2 cos θ
dθ
4 sin2 θ 4 sin2 θ
Z Z
I = p 2 cos θ dθ = 2 cos θ dθ
4 − 4 sin2 θ 2 cos θ
R
= (2 − 2 cos 2θ) dθ = 2θ − sin 2θ + k
x xp x x√
= 2 sin−1 −2 1 − x2 /4 + k = 2 sin−1 − 4 − x2 + k
2 2 2 2
3. a) Put u = 2x dv = e−x dx
dv
∴ = e−x v = −e−x (constant of integration not needed here.)
dx
du
∴ =2 ∴ du = 2dx
dx
Z Z
I = −2xe − (−e ) 2dx = −2xe + 2 e−x dx
−x −x −x
= −2xe−x − 2e−x + k
b) u = x2 dv = cos 4x dx
x2 1
Z
= sin 4x − x sin 4x dx
4 2
x2 x 1
= sin 4x + cos 4x − sin 4x + k
4 8 32
2
c) Put u = tan−1 x ; dv = dx
du 1
= ; v=x
dx 1 + x2
x 1
Z
∴ I = x tan −1
x− dx = x tan−1 x − ln(1 + x2 ) + k
1 + x2 2
(Put z = 1 + x2 for last step.)
d) Put u = (ln x)2 ; dv = dx
du 2 ln x
= ; v=x
dx x
2 ln x
Z
2
I = x(ln x) − x dx
x
Z
2
= x(ln x) − 2 ln x dx = x(ln x)2 − 2(x ln x − x) + k
10
e) Put u = x + 2 ; Zdv = (x + 1) dx
du
=1; v = (x + 1)10 dx
dx
(x + 1)11
= (no constant of integration needed here.)
11
(x + 2)(x + 1)11 (x + 1)11
Z
I = − dx
11 11
3
∴I = 2(1 − e−π ) − 4I
2
∴ 5I = 2(1 − e−π ) ⇒ I = (1 − e−π )
5
1 A B C
4. i) = + 2+
u2 (a + bu) u u a + bu
Multiply by u2 (a + bu)
1 = Au(a + bu) + B(a + bu) + Cu2
1
u=0 1 = aB ∴B =
a
a a2 b2
u=− 1 = 0+0+C ∴C =
b b2 a2
1 b
coefficient of u2 0 = Ab + C ∴A = − C = −
b a2
b 1 1 1 b2 du
Z Z Z
I = − 2 du + du +
a u a u2 a2 (a + bu)
b 11 b
= − ln u − + 2 ln(a + bu) + k
a2 au a
1 dz
Substitute z = x − 2
; =1
dx
x=0 ⇒ z = − 21
x=1 ⇒ z = + 21
1 1 1
dz 1 dz 1 tan−1 2z 2
Z Z
2 2
I = = =
− 12 2z + 1/2
2 2 − 12 z + 1/4
2 2 1/2 −1 2
1 π π π
= [tan−1 2z]−2 1 = − − =
2 4 4 2
x2 + 3x + 1 A B C D
(iii) = + + +
(x + 2)2 (x + 3)2 x + 2 (x + 2)2 x + 3 (x + 3)2
4
x2 + 3x + 1 = A(x + 2)(x + 3)2 + B(x + 3)2 + C(x + 2)2 (x + 3) + D(x + 2)2
x = −2 −1 = B
x = −3 1 = D
coefficient of x3 0 = A+C
constants 1 = 18A + 9B + 12C + 4D = 18A − 9 + 12C + 4
∴A = 1; C = −1
1 1
I = ln(x + 2) + − ln(x + 3) − +k
(x + 2) (x + 3)
x3 = x2 ⇒ x2 (x − 1) = 0 1
∴ x = 0 or 1. x2 x3
R1 R1
∴ Area = 0 x2 dx − 0 x3 dx 0
-1 0 1
1 4 1
x3
x 1 1 1
= − = − =
3 0 4 0 3 4 12 -1
4 4/x2
= 5 − x2 ⇒ 4 = 5x2 − x4 6
x2
x4 − 5x2 + 4 = 0
5-x2
3
2 2
(x − 4)(x − 1) = 0
∴ x = ±1 or ±2. 0
R2 4
R2 -3 -2 -1 0 1 2 3
∴ Area on RHS = 1 (5 − x2 ) dx − 1 2 dx
x -3
2 2
x3
4 8 1 4 2
= 5x − − − = 10 − −5+ + −4 =
3 1 x 1 3 3 2 3
4
Total area = .
3
5
Rπ
c) A= 0
e−x sin x dx
1
π Rπ
= [−e−x sin x]0 − 0 (−e−x ) cos x dx
e-x
Rπ
= 0 + 0 e−x cos x dx
π Rπ
= [−e−x cos x]0 − 0 (−e−x )(− sin x) dx
Rπ
= e−π + 1 − 0 e−x sin x dx e-x sin x
0
∴A = e−π + 1 − A 0 1 x 2 3
1 −π
∴A = (e + 1).
2
1 2
x2 + y 2 = 1 and y=
2
A
1 2
1 P Q
∴ x2 + = 1 2
4 0
-1.5 0 1.5
√
3 -1
x = ± .
2
-2
√ √
3 3
Z
2 √ Z
2 1
Area = 1 − x2 dx − dx (clearly y is +ve on PAQ)
√
− 23
√
− 23 2
√
3 √
Z
2 √ 3
= 1 − x2 dx −
−
√
2
3 2
√
3 1 2π 2π
= − + sin + = 0.6142
2 2 3 3